1996
DOI: 10.1093/oxfordjournals.humrep.a019012
|View full text |Cite
|
Sign up to set email alerts
|

Oolemma characteristics in relation to survival and fertilization patterns of oocytes treated by intracytoplasmic sperm injection

Abstract: The aim of this study was to analyse the various reactions displayed by the oolemma to the penetrating pipette during intracytoplasmic sperm injection (ICSI) and correlate them with clinical factors, oocyte survival and fertilization patterns. Three types of oolemma responses were observed: normal breakage, when the injection needle created an invagination that ruptured at the approximate centre of the egg; sudden breakage, when the membrane broke without creating a funnel; and difficult breakage, when the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
3
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 16 publications
6
74
3
1
Order By: Relevance
“…1b). For the consideration of injection parameters, we awarded three points to oocytes in which the ICSI pipette encountered some resistance and which the removal of the pipette left a visible 'funnel' for at least 30 s; oocytes in which a considerable amount of resistance was encountered before plasma membrane rupture were awarded two points and oocytes in which no resistance to the ICSI pipette was encountered were awarded one point ( [46], Fig. 1c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). For the consideration of injection parameters, we awarded three points to oocytes in which the ICSI pipette encountered some resistance and which the removal of the pipette left a visible 'funnel' for at least 30 s; oocytes in which a considerable amount of resistance was encountered before plasma membrane rupture were awarded two points and oocytes in which no resistance to the ICSI pipette was encountered were awarded one point ( [46], Fig. 1c).…”
Section: Methodsmentioning
confidence: 99%
“…Human oocytes may contain inclusions or vacuoles which may be detrimental to the implantation potential of this material [37,38,[41][42][43]. The oocyte plasma membrane response to penetration with an ICSI pipette has also been suggested to be a useful determinant of oocyte quality [46]. Many other parameters have also been analysed in oocytes such as zona pellucida thickness, spindle birefringence and extracellular dysmorphisms [36,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Following this attempt, four years later, Palermo et al (1992) first reported human pregnancies after ICSI [2]. Since then, ICSI has progressively replaced the previous techniques of gamete micromanipulation as the treatment of choice in cases of male factor infertility and those of failed conventional IVF cycles [3]. Given the widespread use of ICSI, any modifications that can improve its clinical outcomes could possibly benefit a large segment of the patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficiency of ICSI has been clearly demonstrated [2,4,5], this procedure is typically associated with the degeneration of a significant percentage of treated oocytes [2,3,6,7]. The main cause of this degeneration remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation